Perencanaan Aplikasi Antrian Dokter Pada Klinik Bhakti Asih - Rachmadi Setiawan; Gilang Putra R.; Rian Pradifta S.; Thoyyibah. T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
General practitioner service locations often have many patients queuing for treatment. This is inefficient because there is not enough waiting time for rest or other activities. Because of these problems, we need a technology that facilitates patient queues. In this post, we will design an online queuing application that is divided between two users. That is, the queue on the patient's side uses an Android-based application. The output of this queuing system application can run the queue process online via an Android smartphone, and also provides a notification function, so that when the next queue number is called, the patient will get a reminder in the form of an Android notification. accept. To quickly move to the next queue number Return to the doctor's location.